Framework to discuss corruption in OECD Economic Surveys - Jin, Yosuke (OECD Economics Department Working Papers, 2021)
The abuse of public office for private gains - discourages business dynamism, reducing investment and innovation, and weighs on growth prospects. It also undermines the equality of opportunities, distorts the income distribution and erodes trust in government. Corruption is often closely associated with other economic crimes such as tax evasion and money laundering. Corruption takes diverse forms such as bribery and abuse of functions, and is often a multi-faceted phenomenon. It prevails through many different mechanisms, stemming from deficiencies in specific policy areas under weak constraints against corrupt behaviour. Therefore, successfully combatting corrupt behaviour requires a comprehensive approach, addressing a wide range of policy areas. The framework developed in this paper explores in detail how corruption is associated with different policy settings. This framework also makes the most use of the existing corruption indicators, which reflect different understandings of corruption, in order to identify priority policy areas for each country. This framework aims to serve as a pathway to orient OECD Economic Surveys to state-of-the-art policy discussions which have been increasingly matured in each policy area within the Organisation